Choroidal Metastasis from Follicular Thyroid Carcinoma: A Rare Case Report (Bangladesh Journal of Nuclear Medicine, 2018)
Follicular thyroid carcinoma is the second most common thyroid carcinoma and causes distant metastasis more frequently than any other types. Choroidal metastasis from follicular thyroid carcinoma is extremely rare. Only a few cases have been reported since 1979. We present the case of a 60 years old woman developing choroidal metastasis with associated local (lymph nodes) and distant (lungs) metastasis after nine years of diagnosis as primary follicular carcinoma.Bangladesh J. Nuclear Med. 20(2): 155-158, July 2017